2012
DOI: 10.1159/000342875
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Study in a Mutant of Triatoma infestans (Hemiptera: Reduviidae) Carrying a Spontaneous Autosomal Fusion and an Extra Chromosome

Abstract: Triatomainfestans (2n = 20 A + XY, male) is a blood-sucking bug and the most important vector of Chagas disease in the Southern Cone countries. A cytogenetic analysis of 14 individuals from the Argentine Gran Chaco has revealed the presence of a naturally heterozygous for an autosomal fusion. The fusion heterozygote (2n = 19 A + 1 extra chromosome + XY, male) presented an autosomal trivalent, 8 bivalents, the X and Y sex univalents, and a minute extra chromosome at meiosis I. The autosomal trivalent divided eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…We also observed that in E. cornutus the position of a CMA 3 + dot was terminal, while in E. heros this dot was intercalary. This is some evidence of the importance of chromosome rearrangements in Pentatomidae, even when compared with large rearrangements described for the Reduviidae T. infestans [Poggio et al, 2013].…”
Section: Discussionmentioning
confidence: 64%
“…We also observed that in E. cornutus the position of a CMA 3 + dot was terminal, while in E. heros this dot was intercalary. This is some evidence of the importance of chromosome rearrangements in Pentatomidae, even when compared with large rearrangements described for the Reduviidae T. infestans [Poggio et al, 2013].…”
Section: Discussionmentioning
confidence: 64%
“…Rearrangements are more precisely evidenced when trivalents, multivalents or robust cytogenetic markers (heterochromatin, rDNA sites or others) are noted. Samples of these events were reported for species of Belostoma Latreille, 1807 (Papeschi 1994, 1996) and Triatoma infestans (Klug, 1834) (Poggio et al 2013b). Other examples of chromosome changes were reported in insects of the family Aradidae, where fusions were important for karyotype evolution (Jacobs 2003), as well as the dysploidy that originated the neoXneoY sex system in Dysdercus albofasciatus Guérin Meneville, 1831 (Bressa et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 36 species of Pentatomomorpha studied until now, the rDNA loci are preferably located in autosomes with only four species with rDNA loci on the sex chromosomes (González-García et al 1996, Bressa et al 2009, Grozeva et al 2011, Bardella et al 2013). On the contrary, in Cimicomorpha, the location of rDNA loci are more heterogeneous: the hybridization sites are observed on autosomes, sex chromosomes or both simultaneously (Dias de Campos Severi-Aguiar and Azeredo-Oliveira 2005, Severi-Aguiar et al 2006, Morielle-Souza and Azeredo-Oliveira 2007, Grozeva et al 2010, 2011, 2013, 2014, Panzera et al 2012, 2014, Poggio et al 2011, 2013a, 2013b). …”
Section: Introductionmentioning
confidence: 99%
“…However, the present analysis of mutant organisms revealed peculiar behavior during meiosis: chromosomes condensed and did not show chiasms, chromatin bridges were observed between the autosomes, and some homologous chromosomes did not pair. Cytogenetic analysis of T. infestans mutants was also recently conducted in a previous study that revealed spontaneous fusion and an extra autosomal chromosome in these organisms (Poggio et al, 2013). Noireau et al (1998) proposed that cryptic speciation is occurring among populations of Chicago-Bolivian T. sordida, based on evidence of reproductively isolated populations.…”
Section: Discussionmentioning
confidence: 99%